Paleogeographic Reconstructions of Productive Deposits of the Parfenovsky Horizon on the Territory of the Angara-Lena Step of the Southeastern Siberian Platform - E. S. Iz’yurova; O. V. Postnikova; A. D. Iz’yurov; O. A. Zueva; V. V. Rybalchenko; A. S. Smirnov (Georesursy, 2025)
Based on the results of lithological, cyclostratigraphic analyses, as well as linking with geophysical research of wells data and correlation of well sections, the main isochronous levels of deposits of the Parfenovsky horizon in different facies zones of the Angara-Lena step were identified and traced. The sediments were formed in the conditions of coasts with wandering streams and tidal deltas passing into a shallow marine sedimentation basin. The lithological heterogeneity of the deposits is associated with a wide variety of medium-scale facies units (meso-facies), as well as the intensity and direction of secondary processes.